UPAYA PENERAPAN HYGIENE DAN SANITASIDI GARDEN CAFÉ KITCHEN PADA HOTEL GRAND HYATT NUSA DUA BALI - Sumerta, I Ketut Eli Sumerta; Krisnadhi, William; Irwanti, Ni Ketut Dewi (HARMONY HOSPITALITY, 2023)
The background of the research are lack of hygiene and sanitation in personal hygiene, food hygiene, and kitchen hygiene in the Garden Café kitchen at the Grand Hyatt Nusa Dua Bali. Therefore, the author raises the title of research on the application of hygiene and sanitation Garden Café Kitchen at the Grand Hyatt Nusa Dua Bali. The aims and benefits of the authors are to be wise and prudent in applying hygiene and sanitation in the Garden Café kitchen. In this study, the authors used qualitative data from primary and secondary data sources. Using research instruments to improve research results. The instrument were used in this research were observation, interviews and documentation, and also using qualitative descriptive data analysis techniques. The result of the study shows that efforts are made to apply hygiene and sanitation, namely providing hygiene and sanitation SOPs and daily HACCP in the Garden Café kitchen. The obstacles in this research namely  the number of staff who are undisciplined and do not comply with the standard procedure operational given by the management as well as problems that occur with food hygiene and kitchen hygiene, several methods have been carried out by management by holding staff training and weekly briefings and direct warnings for staff who still violate operational working hours. For kitchen hygiene, report directly to other departments to get direct treatment.